ORGANIZATIONAL AND GEOGRAPHIC ACCESSIBILITY: OBSTACLES BETWEEN USERS WITH TUBERCULOSIS AND HEALTH SERVICES - Rosana Huppes Engel; Teresinha Heck Weiller; Elaine Miguel Delvivo Farão; Iarema Fabieli Oliveira de Barros; Juliana Bordignon; Emanuelli Mancio Ferreira da Luz (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976928494 Aim: the study aimed to identify the geographical and organizational accessibility of Tuberculosis (Tb) patients at a city of the central area of Rio Grande do Sul. Method: the sample was formed by seventy addresses of Tb patients at the period of 1999 and 2008. Information were obtained from geographical and territorial boundaries of the Brazilian Institute of Geography and Statistics(IBGE). Results: eighty percent of the patients live far of the basic health unit and, over seventy percent of them live n streets with difficult access. Conclusion: the access to health services is made by forming lines in order to distribute patient charts for treatment, showing organizational problems regarding the tuberculosis patients. Geographical and organizational accessibility needs to be discussed by managers and healthcare practitioners in order to guarantee the integrality of treatment.